Inorganic Fertilizer Application and Organonitrofos Sugarcane (Saccharum officinarum L.) in Dry Land Gedong Meneng - Zulkarnain, Eldineri; Evizal, Rusdi; Lumbanraja, Jamalam; Rini, Maria Viva; Satgada, Catur Putra; Agustina, Wiwik; Amalia, Hanum Riajeng; Awang, Tegar Rafshodi (Jurnal Penelitian Pertanian Terapan, 2017)
Organonitrofos is one type of organic fertilizer capable of providing macro nutrients that more than other organic fertilizers, particularly nitrogen and phosphorous from the compost of a mixture of fresh manure and rock phosphate using Microbial N2-fixer and P-solubilizer. Research purpose was to study the effect of organonitrophos combined with inorganic fertilizer on the growth, production, yield of sugarcane, and determining the most effective combination of agronomically and economically in up landsugarcane. Research consisted of 5 treatments with 3 replications arranged in a randomized complete block design. The treatment were A (300 kg ha-1 Urea, 150 kg ha-1 TSP, 300 kg ha-1 KCl), B (300 kg ha-1 Urea, 150 kg ha-1 TSP, 300 kg ha-1 KCl, 5,000 kg ha-1 Organonitrophos), C (150 kg ha-1 Urea, 75 kg ha-1 TSP, 150 kg ha-1 KCl, 10,000 kg ha-1 Organonitrophos), D (10,000 kg ha-1 Organonitrophos), and E (without fertilization). The results showed that the dose of fertilizer recommendation (300 kg ha-1 urea, 150 kg ha-1 TSP, 300 kg ha-1 KCl) supplemented with 5 ton ha-1 Organonitrofos compared to the doses of fertilizer recommendation (300 kg ha-1 Urea, 150 TSP kg ha-1, 300 kg ha-1 KCl) was not significantly different on growth, yield, productivity of sugarcane and sugar. While the addition of 10 ton ha-1 Organonitrofos at half dose of recommendation (150 kg ha-1 urea, 75 kg ha-1 TSP, and 150 kg ha-1 KCl) produced 106.11 tons ha-1of sugarcane and 7, 95 ton ha-1sugar being lower than the dose of fertilizer recommendation that produced 133.02 tons ha-1sugarcane and 10.72 ton ha-1 sugar resulting macro nutrients derived from half dose of fertilizer recommendation are not able to increase the productivity of sugarcane and sugar.Dose of fertilizer recommendation plus 5 ton ha-1 Organonitrofos was an effective dose of fertilizer agronomically while fertilizer dosage recommendation was the most efficient dose of fertilizer economically.Keywords :dry land, fertilizer, inorganic, Organonitrophos, sugar cane